Agriculture at the crossroads : challenges of food security and rural development in Siaya County - Juma, Dorothy Roseline (SLU/Dept. of Urban and Rural Development, 2019)
Africa is always being, portrayed as a continent of poverty and one that needs to develop, and increase its food production. The quest has lead world organizations to launch projects for development and economic growth in Africa where majority are poor. The many years of investment project and programs in development has not yielded much to the alleged poverty. Most countries of Sub Sahara Africa depend on agriculture for subsistence and economic growth. Agricultural production is by small-scale holder farmers, living in rural areas where most are poor and food insecure, despite the contribution to their country’s economy. Why has the many years of poverty eradication not yielded improvement to the alleged high poverty levels? This study considers poverty as structural, the perspective in which, and poverty is, seen as a resultant of wider structures beyond an individual’s control. The study analyses the role of the prevailing institutions, in agricultural development and poverty eradication. The findings indicate that smallscale farmer’s livelihood is, challenged not only by nature, but also by unfavourable institutions that risk their vulnerability to poverty and food insecurity.